RHEOLOGICAL CHARACTERIZATION OF RECLAIMED ASPHALT BINDER BLENDED WITH THE NEAT AND SBS-PMA BINDERS - AMEEN, MUSTAFA AMEEN; ABDULRAZAQ, BAYAR NAJEEB; AL-HADIDY, ABDUL AL-RAHIM I. (Journal of Duhok University, 2023)
Reusing reclaimed asphalt pavement material guarantees a substantial optimization of non-renewable material resources, emissions reduction, and decreasing landfill space, along with the economic benefits associated with saving the costs of purchasing and transporting new aggregate and asphalt binder for asphalt concrete mixture production. This study aims to investigate the influence of aged asphalt binder from reclaimed asphalt pavement on the virgin asphalt binder’s rheological properties. Therefore, different dosages of RAP binder (20%, 30%, and 40% by weight of the total mix) were blended with neat asphalt binder (40-50), penetration grade (P40), and SBS polymer asphalt (SBS-PMA) binder. Using both traditional and Superpave performance testing methods, the effects of RAP on the blend’s consistency, viscosity, softening, elastic recovery, rutting (permanent deformation), fatigue cracking, and low temperature cracking were evaluated. The results revealed that the RAP binder decreased the penetration value of both neat and SBS-PMA binders. The neat asphalt binder’s viscosity and softening point increased with the increase in RAP content, whereas they decreased for SBS-PMA. The RAP binder decreases the SBS-PMA elastic recovery. where the neat asphalt experienced a little improvement in elastic recovery when blended with the RAP binder. The Superpave test results revealed that the RAP binder deteriorates the performance of the SBS-PMA binder at high, intermediate, and low testing temperatures. With the addition of 20%, 30%, and 40% RAP, the high-temperature PG grade of SBS-PMA blends decreased by 0.64%, 0.95%, and 1.10%, respectively, while the low-temperature PG grade increased by 23%, 31%, and 32%, respectively. In contrast, the RAP improves the neat asphalt blend’s high-temperature performance grade and deteriorates intermediate and low-temperature performance grades. The addition of 20%, 30%, and 40% RAP increased the neat asphalt blends’ high-temperature properties by 1.5%, 3.3%, and 4.5%, respectively. whereas the neat asphalt low-temperature PG grade increased by 5%, 11%, and 15% with the addition of 20%, 30%, and 40% RAP, respectively. In summary, the performance of virgin and RAP binder blends depends on the individual characteristics of the blended asphalt binders